Healthcare interventions for the prevention and control of gestational diabetes mellitus in China: a scoping review - Tingting Xu; Yasheng He; Livia Dainelli; Kai Yu; Patrick Detzel; Irma Silva-Zolezzi; Sheri Volger; Hai Fang (BMC, 2017)
Abstract Background Gestational Diabetes Mellitus (GDM) is a type of diabetes which occurs during pregnancy. Women with GDM are at greater risk of complications during pregnancy and delivery, while babies born from mothers with GDM are at greater risk of post-natal complications. Using the most updated diagnosis criteria, the GDM prevalence is estimated at 9.3-25.5% worldwide and 9.3-18.9% in China. Our objective was to identify healthcare interventions aimed at GDM prevention and control in China. Methods A best-evidence synthesis was performed based on a systematic search of literature published between 1997 and October 2015 in PubMed, Web of Science, China National Knowledge Infrastructure (CNKI), and Wan-fang databases using keywords "Gestational Diabetes Mellitus", "GDM", "Intervention" "Medical Intervention" "Early Medical Intervention", "Dietary Intervention", "Exercise Intervention", "Lifestyle Intervention", "Therapy", "Treatment" and "China". Inclusion criteria were studies conducted in China, reporting GDM healthcare interventions, and published in either Chinese or English. Two reviewers independently assessed eligibility and quality of the studies and extracted the data. Treatment efficacy was examined with weighted pooled odds ratio (OR) meta-analyses. Results The search resulted in 5961 articles (published in 276 different Chinese language journals and 6 English language journals), of which 802 were included in this synthesis. While 39.4% (n = 316) failed to report the GDM diagnostic criteria used, the remaining studies classified GDM with various international (n = 5) or Chinese (n = 7) diagnostic standards. Treatment interventions were categorized into 6 types: dietary (18.6%), exercise (1.6%), medication (20.7%), health education (9.0%), psychological (2.6%) and combination (47.4%). No interventions aimed at GDM prevention were identified. Meta-analyses demonstrated a statistically significant overall benefit of GDM treatment strategies in reducing the odds of maternal and infant adverse outcomes (ORs range 0.20-0.34, 95% CI 0.17-0.49, P < 0.05 for all). Dietary, western medication, and combined interventions were the most effective inteventions. Conclusions An increasing number of healthcare interventions were found in China aimed at controlling GDM while no interventions were intended for GDM prevention. Well-designed clinical trials are needed to determine the comparative and cost effectiveness of GDM prevention and treatment strategies.